Campur Kode Cinta Laura Kiehl dalam Talk Show Just Alvin di Metro TV (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
Cinta Laura Kiehl as a woman who is still young, creative, and has different characteristics from the others. The most prominent characteristics of her is the way she speaks or her accent and also the mix of languages she use every day. The language she uses is mixed between Indonesian and English. Because in fact she is an Indonesian national. However, she was born in Germany and spent much of her time abroad, for example, she studied at Colombia University, United States. Therefore, she uses a lot of mixed languages. Mixing code or language is what is studied in the field of sociolinguistics. This study aims to describe the form and causes of code mixing in interviews. This study used a qualitative descriptive design. The data source of this research is Cinta Laura Kiehl of utterances that were interviewed exclusively in Talk Just Alvin on Metro TV on Friday, September 13, 2013. The results of this study, firstly, form of code mixing between Indonesian and English. The two cause of code mixing include role factors, variety factors, speaker factors, and language factors.